Evaluate the effects of low-intensity pulsed ultrasound on dental implant osseointegration under type II diabetes - Wang, Yingying; Cao, Ximeng; Shen, Yingyi; Zhong, Qi; Wu, Ziang; Wu, Yaqin; Weng, Weimin; Xu, Chun (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: The objective of this study is to assess the impact of low-intensity pulsed ultrasound (LIPUS) therapy on the peri-implant osteogenesis in a Type II diabetes mellitus (T2DM) rat model.A total of twenty male Sprague-Dawley (SD) rats were randomly allocated into four groups: Control group, T2DM group, Control-LIPUS group, and T2DM-LIPUS group. Implants were placed at the rats' bilateral maxillary first molar sites. The LIPUS treatment was carried out on the rats in Control-LIPUS group and T2DM-LIPUS group, immediately after the placement of the implants, over three consecutive weeks. Three weeks after implantation, the rats' maxillae were extracted for micro-CT, removal torque value (RTV), and histologic analysis.Results: Micro-CT analysis showed that T2DM rats experienced more bone loss around implant cervical margins compared with the non-T2DM rats, while the LIPUS treated T2DM rats showed similar bone heights to the non-T2DM rats. Bone-implant contact ratio (BIC) were lower in T2DM rats but significantly improved in the LIPUS treated T2DM rats. Bone formation parameters including bone volume fraction (BV/TV), trabecular thickness (Tb.Th), bone mineral density (BMD) and RTV were all positively influenced by LIPUS treatment. Histological staining further confirmed LIPUS's positive effects on peri-implant new bone formation in T2DM rats.As an effective and safe treatment in promoting osteogenesis, LIPUS has a great potential for T2DM patients to attain improved peri-implant osteogenesis. To confirm its clinical efficacy and to explore the underlying mechanism, further prospective cohort studies or randomized controlled trials are needed in the future.